HOW PHYSICALLY ACTIVE ARE SPORTS EXPERTS? - Branko Đukić; Branislav Strajnić; Goran Glamočić; Vladimir Ivanek (Sport Scientific And Practical Aspects, 2025)
Through their actions and behavior forms, coaches set an example for the athletes they work with, and additionally oblige them to lead a healthy lifestyle, which includes a proper diet and regular physical activity manifested in various forms. The aim of the paper is to compare the categories of physical activities between male and female sports experts. The results of the research showed that 63% of trainers practice high physical activity, and 36% moderate physical activity, with women applying high physical activity by 6.8% more than male sports experts. Observed physical activity is expressed in MET units (metabolic equivalent of task). The analysis of the chi-square test did not show a statistically significant difference in the representation of physical activity categories among male and female sports experts. The observed level of physical activity (light, moderate, heavy, total physical activity), analyzed using the t-test for independent samples, did not show a significant difference between male and female coaches.